Memory and narrative at the origin of the novel three studies, from Chrétien de Troyes to Proust - Mainini, Lorenzo (Routledge, 2024)
This book investigates certain recurrent structures in the history of the novel as a textual genre and as a narrative form typical of Western literature. From its origins, in the vernacular cultures of the twelfth and thirteenth centuries, the novel text seems to be characterised by certain stylistic procedures adopted to represent a new narrative framework, which has no direct terms of comparison in the previous literary tradition. Indeed, the novel, as a 'textual machine', often produces a 'narrative manipulation' of time and duration, to the point of establishing, along its development, a very close link between History, individual memory and a prospective narrative future. This book explores some structural and formal paths of the 'novelistic machine', through three exemplary cases: (1) the 'name of the novel' at the origins of the literary genre, with the invention of a new 'novelistic technique' (i.e. the conjointure) by Chrétien de Troyes (twelfth century); (2) the bookform, namely, 'the book of novels' as a concrete and material object that transmits the narrative text and involves itself within the fictional universe; (3) the literary topos of the 'dreaming incipit' and its long history from the Roman de la rose to Proust. This book will be of significant interest to students and scholars of medieval literature, the history of the novel and philology.
Revision of English text by Richard Bates
Keywords: Geschichte; Französisch; Erinnerung -- Motiv; Roman; Poetik; Fiction-History and criticism; Memory in literature; Narration (Rhetoric)